A novel chemical looping partial oxidation process for thermochemical conversion of biomass to syngas. (15th July 2018) - Xu, Dikai; Zhang, Yitao; Hsieh, Tien-Lin; Guo, Mengqing; Qin, Lang; Chung, Cheng; Fan, Liang-Shih; Tong, Andrew
Graphical abstract: Highlights: Demonstrated chemical looping process using moving bed for biomass gasification. Experimentally verified syngas production at high purity from woody biomass. Proved multiple syngas conditioning units are not required for BTS process. Process simulation shows significant reduction in biomass and water consumption. The new process shows the potential to reduce renewable energy production cost. Abstract: The Biomass-to-Syngas (BTS) chemical looping process is an advanced thermochemical biomass conversion process for the production of sustainable fuels and chemicals. The BTS process is novel in that it converts biomass feedstock to high purity syngas with adjustable H2 :CO molar ratio without needing an air separation unit (ASU), a tar reformer, a steam reformer, or a water-gas-shift (WGS) reactor. In the BTS process, biomass feedstock is partially oxidized to produce syngas by oxygen carriers in a reducer that is operated in a co-current gas-solid moving bed contact mode. The reduced oxygen carriers are regenerated in a fluidized bed combustor via the oxidation reaction with air. The BTS process uses the iron-titanium composite metal oxide (ITCMO) material as the oxygen carrier, which is capable of cracking the volatiles produced in biomass pyrolysis as well as regulating the syngas composition. The co-current moving bed reducer eliminates back-mixing, channeling, or bypassing of solid and gas reactants, resulting in a syngas composition that is close to the thermodynamic equilibrium. In this paper, the rationale of a successful BTS process is discussed along with the thermodynamic characteristics of the ITCMO oxygen carrier, that can effectively react with a woody biomass feedstock, analyzed based on an ASPEN Plus model. Bench scale moving bed reducer experiments are presented, indicating the conversion of wood pellets to syngas with a H2 :CO ratio of 2, which is suitable for methanol or liquid fuel synthesis. The gas and solid composition produced in the bench scale reducer matches the prediction from the ASPEN Plus thermodynamic model. This model is further used to analyze the performance of the BTS process under autothermal conditions for methanol production, with a comparison with a baseline indirectly heated gasification process. The results indicate that the BTS process significantly reduces the biomass and steam consumption and appreciably improves the biomass conversion efficiency over that obtained from the baseline process.